Intercultural education in Kosovo: A longitudinal case study - Cameron White; Blerim Saqipi (Journal of Education and Learning (EduLearn), 2021)
This longitudinal qualitative study was conducted with Kosovo PhD students over a 3-year period who engaged in an ongoing intercultural education project at the University of Pristina’s Faculty of Education in Kosovo. The purpose of this article is to deepen the understanding of intercultural education with Kosovo as a critical case study. The data included pre-and post-open-ended surveys, one on one interviews, and follow up interviews regarding intercultural education during the longitudinal experiences. The findings of the study suggest the need to contextualize the issues of intercultural education and integrate local to global connections in relevant teaching, research, and service.